The Quadratic Oil Extraction Oligopoly - John Hartwick (Queen's University, Department of Economics, 2006)
Each extractor has a distinct quadratic extraction cost and faces a linear industry demand schedule. We observe that the open loop and closed loop solutions are the same if initial stocks are such that each competitor is extracting in every period in which her competitors are extracting.
Keywords: D43; Q32; 330; oligopoly extractors; closed loop solution